LЕGАL STАTUS ОF THЕ SPЕCІАL SОCІАL CЕNTЕRS FОR THЕ ЕLDЕRLY АND DІSАBLЕD ІN THЕ RЕPUBLІC ОF KАZАKHSTАN (Journal of actual problems of jurisprudence, 2019)
The article analyzes the complex system of solving problems arising in connection with the legal status of boarding schools for the elderly and disabled (boarding houses) in the Republic of Kazakhstan and the protection of the rights of elderly citizens living in them. Analyzing the norms of the law defining the legal form and structure of residential homes for the elderly and disabled (boarding houses) in the country, an analysis was made of the activities and main goals of existing social institutions serving elderly citizens. Thus, the analysis of international experience in the protection of the rights of elderly people living in boarding houses for the elderly and disabled, scientific works of foreign scientists and domestic scientists in the field of protection of the rights of elderly citizens in developed civilized foreign countries, analysis of compliance with national laws international standards related to the protection of the rights of senior citizens in the Republic of Kazakhstan. The norms of international law conducted an analysis of the observance in the Republic of Kazakhstan of the principles and standards recognized by many states of the world in the field of human rights protection. It also analyzed the legal powers of state bodies and public organizations in the Republic of Kazakhstan related to the protection of the rights of elderly people living in boarding houses (boarding houses) for the elderly and disabled. Key words: law, elderly people, law, state, social protection, pensions.